2017
DOI: 10.3344/kjp.2017.30.4.250
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and fibromyalgia: a meta-analysis

Abstract: Vitamin D is a cofactor responsible for autoimmune disorders. There is no agreement in the studies investigating the association between vitamin D and fibromyalgia. This study aims to combine the conflicting results of the primary studies which compared these patients with control groups regarding the serum concentration of vitamin D. This meta-analysis has been designed based on PRISMA guidelines. Relevant keywords were searched in PubMed, Science direct, Scopus, Cochrane, and Google scholar and primary studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 24 publications
(44 reference statements)
1
27
0
5
Order By: Relevance
“…The nutritional preparation was selected from the current literature (Pubmed, Uptodate, and Google Scholar) using the keywords fibromyalgia and nutraceutical treatment. The literature reported efficacy evidence in FMS for coenzyme Q10, vitamin D, alpha-lipoic acid, magnesium, and tryptophan [7,[12][13][14][15]. Considering the nutraceutical composition and properties, the best therapeutic option was found to be a nutritional product containing all the substances considered above (Migratens ® , Laborest srl, Assago, Milano, Italy).…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional preparation was selected from the current literature (Pubmed, Uptodate, and Google Scholar) using the keywords fibromyalgia and nutraceutical treatment. The literature reported efficacy evidence in FMS for coenzyme Q10, vitamin D, alpha-lipoic acid, magnesium, and tryptophan [7,[12][13][14][15]. Considering the nutraceutical composition and properties, the best therapeutic option was found to be a nutritional product containing all the substances considered above (Migratens ® , Laborest srl, Assago, Milano, Italy).…”
Section: Interventionsmentioning
confidence: 99%
“…In FMS patients, the role of vitamin D deficits and supplementation is controversial. In some systematic reviews, a correlation between vitamin D deficiency and fibromyalgia was determined, whereas its role in the pathophysiology and its clinical relevance requires further controlled studies [12,49]. More recent reviews reported as inconclusive the relationship between hypovitaminosis D and FMS, although vitamin D supplementation was considered as a co-adjuvant in FMS therapy [50].…”
Section: Nutrient Considerationsmentioning
confidence: 99%
“…Based on what was discussed above, therefore, a lower level of cortisol in the circulation could be connected with a condition of dysbiosis in which there is an increase in the genus of Ruminococcus: both situations have been described in the patient with FM. • Vitamin D. In the patient with FM, a lower concentration of vitamin D3 was noted [33][34][35] and it appears to lead to an increase in chronic pain, one of the most serious symptoms of the disease. Vitamin D is able to reduce pain by releasing cytokines 36 or reducing the sensitivity of nerve fibers in the muscles 37,38 .…”
Section: Altered Hormones and Dysbiosis In Fibromyalgic Patientsmentioning
confidence: 99%
“…Literatürde FMS ile vitamin D düzeyi ve vitamin D düzeyinin kliniğe etkisini inceleyen çalışmalar olmakla birlikte, FMS ve vitamin D düzeyi arasındaki ilişki konusunda tam bir fikir birliği yoktur (8,9,(14)(15)(16)(17)…”
Section: Discussionunclassified